2015
DOI: 10.1371/journal.pone.0140215
|View full text |Cite
|
Sign up to set email alerts
|

Filtration of Macrophage Migration Inhibitory Factor (MIF) in Patients with End Stage Renal Disease Undergoing Hemodialysis

Abstract: BackgroundEnd stage renal disease (ESRD) patients are characterized by increased morbidity and mortality due to highest prevalence of cardiovascular disease. Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine that controls cellular signaling in human physiology, pathophysiology, and diseases. Increased MIF plasma levels promote vascular inflammation and development of atherosclerosis. We have shown that MIF is associated with vascular dysfunction in ESRD patients. Whether hemodialysis (HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In experimental sepsis models, MIF inhibition by MIF antibodies and MIF receptor antagonists was shown to protect from septic shock and to improve survival [ 9 , 33 , 34 ]. We recently showed that hemodialysis is an effective tool to neutralize circulating MIF by removal from the blood pool in patients with end-stage renal failure [ 18 ]. In the present study, we show first evidence of the effect of lowering MIF levels in patients undergoing CRRT in septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental sepsis models, MIF inhibition by MIF antibodies and MIF receptor antagonists was shown to protect from septic shock and to improve survival [ 9 , 33 , 34 ]. We recently showed that hemodialysis is an effective tool to neutralize circulating MIF by removal from the blood pool in patients with end-stage renal failure [ 18 ]. In the present study, we show first evidence of the effect of lowering MIF levels in patients undergoing CRRT in septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely to assume that MIF levels are lowered by CRRT since conduction of CRRT is the only obvious MIF-influencing difference between our groups. Furthermore, our group proofed effective removal of MIF by dialysis before [ 18 ]. In addition, the comparison of decrease of MIF levels with decrease of creatinine levels during CRRT showed a close correlation (Additional file 2 : Figure S2) hinting at a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage migration inhibitory factor (MIF) is known as a pleiotropic inflammatory cytokine and has been recognized as a mediator of a number of inflammatory diseases including sepsis and atherosclerosis [ 8 , 9 , 10 , 11 , 12 , 13 ]. It has recently been described that MIF plays a role in NICM, since expression of MIF in myocardial biopsy samples predicted all-cause mortality in NICM patients and was described as a novel additional tool to predict adverse outcome in patients with NICM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that decreased MIF concentration in cancer can induce macrophage polarization from proinflammatory macrophages (predominantly CD11b + /Ly6C high cells) to pro-wound healing macrophages (CD11b + /Ly6C intermediate cells) [33]. The MIF level decreases obviously during CRRT or hemodialysis and can improve the prognosis [23, 34]; however, how it works is still unknown and the MIF plasma pool is reconstituted early after the termination of hemodialysis from unknown sources. Probably the same thing happens during CRRT of septic AKI patients.…”
Section: The Role Of Crrt In Inflammation and Metabolic Adaptation Inmentioning
confidence: 99%